Factors Influencing the Level of Regional Innovation — Qualitative Comparative Analysis - Anna Krakowiak-Bal; Urszula Ziemiańczyk (Barometr Regionalny, 2018)
Innovation is a highly complicated and ambiguous phenomenon. It is also a key element of the competitiveness of companies, regions and nations. The aim of this study is to identify the conditions that most affect regional innovation. This research combines a group of indicators that define some tangible factors of regional development with level of innovation performance. The pathways to facilitate a region’s higher innovativeness are presented. For this purpose, fuzzy set qualitative comparative analysis is adopted. The analysis was performed for two different groups of regions: Innovative Leaders and Modest Innovators (according to the Regional Innovation Scoreboard). The main findings indicate that there is no single condition that improves innovative performance. It is always a combination of several variables. Having higher GDP, increasing employment in science and technology sectors, improving internet access and taking care of higher education of the population, regional innovativeness will grow. Social conditions such as inhabitants’ age do not show significant impact on regional innovation compared with other factors.